ANALISIS YURIDIS TERHADAP PUTUSAN NOMOR.553/PID.B/2019/PN.Pbr TERHADAP TINDAK PIDANA PEMERASAN - Vitta Adelina Hutasoit; Evi Deliana; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Judge's decision is a judge's statement uttered in an open court session, which can be in the form of conviction or acquittal or exemption from all legal claims in matters and according to methods regulated in the Criminal Procedure Law In criminal procedural law, the objectives are set forth in the guidelines for the implementation of the Criminal Procedure Code issued by the Minister of Justice, namely: "The purpose of criminal procedural law is to seek and obtain or at least approach the material truth, which is the complete truth of the case. a criminal case by applying the provisions of criminal procedure law honestly and appropriately by finding out who the perpetrator can be accused of committing a violation of the law, and then requesting an examination and a court decision from the court to find out whether it is proven that a criminal act has been committed and whether the person accused is can be blamed. " Judges' court decisions play an important role in upholding legal certainty and justice. Decisions in court are given by judges examining cases in the provisions of Article 5 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power, indicating that "judges as law enforcers are obliged to explore, follow and understand the values of law and the sense of justice that lives in Public."Supposedly, it is the judge's duty to make those values real, especially the value of justice. So, the judge's decision should reflect the reflection of the judge's struggle with legal values and the social, cultural and economic environment. In practice, the way of thinking of judges in deciding cases is still positivistic, not daring to look for other grounds that provide a more sense of justice. In Decision Number 533 / Pid.B / 2019 / PN.Pbr. judges who are supposed to uphold justice, seriously do not consider cases of extortion based on elements of criminal acts as stated in Article 368 of the Criminal Code handled by judges. So that certainty, legal values and a sense of justice are not achieved as is the goal of criminal procedural law.This research will be compiled using the juridical normative type of research, which is research focused on examining the application of legal principles or norms to legal principles. The data collection technique used in this research is literature study. The approach used in this research is to use a normative approach, namely literature law research.The results of the research conducted by the author are first, to find out the basis for the judge's consideration in giving a decision in case Number 533 / Pid.B / 2019 / PN.Pbr against the crime of extortion, secondly the accuracy of the judge in making a decision against the perpetrator of the criminal act of extortion on the verdict case Number 533 / Pid.B / 2019 / PN.Pbr.Keywords: Judge's Decision – Extortion - Justice